Uretero-Nephroscopy Standardization in Mares with Air Insufflation - Pamela Tapia Carreno Dornbusch, Lilian; Strugava, Lucimara; Rodrigues da Silva, Jéssica; Lukascek de Castro, Monalisa; Roque de Barros Filho, Ivan; Montiani Ferreira, Fabiano; Carlos Duque Moreno, Juan; Triches Dornbusch, Peterson (Acta Scientiae Veterinariae, 2024)
Background: Ureteroscopy allows visualization of urethral segments, bladder, and ureteral endings, aiding diagnosis and intervention in various conditions not always evident with other imaging methods. Equine ureteroscopy diagnoses urinary tract diseases like lithiasis, infection, neoplasia, or hematuria. Cystoscopic examination enables targeted interventions like ureteral sampling, bladder biopsy, and urolith fragment removal. This study outlines a technique using flexible retrograde endoscopy in mares, with air insufflation facilitating examination of the ureters and renal pelvis. Materials, Methods & Results: The study was carried out in 12 previously fasted (Food was withheld for 12 h and water was withheld for 6 h before the procedures healthy mares of different breeds (thoroughbred, Criollo and mixed breeds). These animals had an average weight of 439 kg, aged 3-17-year-old. The mares had no recent history of any disease and were considered healthy based on physical examination and routine hematological and biochemical examination. The procedures were carried out at the Veterinary Hospital of the Federal University of Paraná (UFPR), in the Large Animal Sector. The animals were physically restrained and had their tails covered with dressings and bandage material to maintain the perineal area clean. The genitalia and perianal region were washed with running tap water, after which the bladder was emptied by urethral catheter number 20. The mares were sedated and 15 min after sedation a flexible endoscope1 with a diameter of 5 mm and length of 100 cm previously sterilized in ethylene oxide was introduced by the external urethral ostium an endoscope 5 mm in diameter flexible and 100 cm in length was inserted through the urethra into the bladder where the ureteral ostia were identified. With a flexible polyethylene probe containing atraumatic metallic tip, the catheterization of the ureters was performed to guide the insertion of the endoscope to the renal pelvis. The ureter and left kidney were inspected in 8 mares and the ureter and right kidney in 4 mares. No complication or discomfort was observed after the procedure. This study demonstrated for the first time the viability of ureterino-nephroscopy using air insufflation to dilate the ureters in standing mares using a novel diagnostic modality that also allows to perform therapeutic interventions in certain diseases that affect the equine ureters and kidneys. Discussion: Ureteroscopy was performed successfully in mares, which allowed observation to the renal pelvis, although there were some limitations, such as the length of the cystoscope, which was used. In one of the mares, it needed to be about 2 cm longer in order to reach the renal pelvis. The anatomical conformation of the bladder and the ureter of some of the mares prevented the ureteroscope from entering the ureter. In these cases, a metal tube was used, serving as a guide for the endoscope, suspending the bladder and allowing access to the ureter. Lastly, the non-cooperative behavior of one of the mares made it impossible to perform the examination, even with sedation and physical restraint. This animal had to be replaced in this investigation. In this investigation no ureteral or renal changes were found. The authors believe that if abnormalities were present, they would be easily noted, since the ureter and renal pelvis were straightforwardly evaluated and in its entirety. Keywords: equine, ureteroscopy, diagnostic, kidneys, pyelonephritis.